Critical reflections from the millennials on the global action against dementia legacy events. (14th September 2015) - Newman, Kristine; Booi, Laura
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to share information regarding the Global Action Against Dementia Legacy, to critically reflect on the views of the Canadian Young Leaders of Dementia and to strengthen the impact of their voices in the global discussion surrounding dementia. Design/methodology/approach – This offers a critical reflection and review of the innovative intergenerational discussions and solutions offered by younger Canadians – specifically, the Millennial Generation. Findings – The paper provides insights about how change and solutions in dementia actions may be established through intergenerational collaboration. Research limitations/implications – Researchers are encouraged to make room for the voices of younger, less established generations in both discussions and research related to dementia. The younger generations will provide future direction to the Global Action Against Dementia Legacy so it is time to hear their voice too. Originality/value – This paper draws on developments in the Canadian context to highlight the potential of encouraging a less-usual, intergenerational approach to developing engagement, research and solutions in dementia.